Годишна средба за социјални и економски политики на УНИЦЕФ, на тема: Влијанието на глобалната економска криза врз земјите од Централна и Источна Европа (ЦЕИ) и Заедницата на независни држави (ЗНД) и последиците од кризата врз состојбата на децата - Талев, Илија (Ревија за социјална политика/Journal of Social Policy, 2009)
From 14 September to 17 September in Glion, Switzerland, a regional meeting of representatives of UNICEF national offices from the countries of Central and Eastern Europe (CEI), as well as the Commonwealth of Independent States (CIS) was held. The occasion for the meeting was to discuss the impact of the global economic crisis on these countries, as well as the consequences of the crisis on the situation of children in the same. The purpose of this meeting was to share information on the ongoing UNICEF implementation and planned activities in order to mitigate, or completely eliminate the consequences of the crisis on children in these countries, as well as to explore the possibilities for some future joint activities in this sphere.